Factors affecting healthy life style behaviors in workers working at a tea factory - Cuneyt Ardic; Guzin Zeren Ozturk; Erdinc Yavuz (SERNEV, 2018)
Introduction: Theobjective of the present study was to determine educational level of theworkers of a tea factory on occupational health and safety and to reveal thefactors affecting a healthy lifestyle.Methods: The presentdescriptive research was carried out in a tea factory where 352 workers areemployed between December 2016 and January 2017. 303 volunteer workers wereenrolled into the study and a questionnaire form including topics ofsociodemographic characteristics, occupational health and safety (OHS)implementations, health state and working conditions that was developed throughliterature information as well as Healthy Lifestyle Behaviors Scale (HLBS) wereused for data analysis. Results: Ageaverage of the workers who were all male was 39.88±5.53. Among the workers,70.29% were elementary school graduate and more than half of the participants(62.70%) have a middle income (500-1,000 USD). Mean score of HLBS scale was118.00±20.28 points. Average score of the sub-topics was the highest in healthresponsibility item with 22.06 points whereas the lowest score was detected inphysical activity sub-topic. It wasdetected that 64.69% of the workers had an occupational health and safetytraining at least once during their lifetime and 21.78% use a protectiveequipment. Rate of exposure to work-related accidents was detected as 10.57%.